Early Nutrition Programming (in ovo and Post-hatch Feeding) as a Strategy to Modulate Gut Health of Poultry - Jha, Rajesh; Singh, Amit Kumar; Yadav, Sudhir; Berrocoso, Julio Francisco Diaz; Mishra, Birendra (Frontiers in Veterinary Science, 2019)
Healthy gastrointestinal tract (GIT) is crucial for optimum performance, better feed efficiency, and overall health of poultry. In the past, antibiotic growth promoters (AGP) were commonly used to modulate the gut health of animals. However, considering the public health concern, the use of AGP in animal feeding is banned or regulated in several jurisdictions around the world. This necessitates the need for alternative nutritional strategies to produce healthy poultry. For that, several alternatives to AGP have been attempted with some success. However, effective modulation of the gut health parameters depends on the methods and timing of the compound being available to host animals. Routinely, the alternatives to AGP and other nutrients are provided in feed or water to poultry. However, the GIT of the newly hatched poultry is functionally immature, despite going through significant morphological, cellular, and molecular changes toward the end of incubation. Thus, early growth and development of GIT are of critical importance to enhance nutrients utilization and optimize the growth of poultry. Early nutrition programming using both in ovo and post-hatch feeding has been used as a means to modulate the early growth and development of GIT and found to be an effective strategy but with inconsistent results. This review summarizes the information on in ovo and post-hatch-feeding of different nutrients and feeds additives and their effects on gut development, histomorphology, microbiology, and immunology. Furthermore, this review will provide insight on the future of early nutrition programming as a strategy to enhance gut health, thereby improving overall health and production so that the poultry industry can benefit from this technique.